An eigenvalue optimization problem for Dirichlet-Laplacian with a drift - محسن زیوری رضاپور (مدل‌سازی پیشرفته ریاضی)
In this paper, we prove a monotonicity result related to the principal eigenvalue for Dirichlet-Laplacian with a drift operator in a punctured ball.